Identifying Vertically Differentiated Products - Bastos, Paulo (2012)
introduced a product classification scheme that has since been widely used to empirically identify differentiated goods. Using firm-level data on export unit values, we provide direct evidence that this classification is well suited for capturing quality differentiation.